Polyflagellated macrocephalic spermatozoa: failure factor in IVF/ICSI - Mohamed, Fanny; Jean-Marc, Dia; Stephane, Adjoussou; Founzegue, Coulibaly; Minata, Fomba; Edele, Aka; Abdoul, Koffi; Mamourou, Kone (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2017)
The authors report two cases of male infertility characterized by spermatic abnormalities of polyflagellated macrocephalic spermatozoa type affecting the entire gametes population. They demonstrate, on the one hand, the technical limitations of microinjection with such spermatozoa due to the large volume of their head and, on the other hand, the unfavourable outcome of the IVF-ICSI with this type of spermatozoa carrying abnormalities constituent. Molecular analysis of the somatic DNA of these subjects revealed a homozygous c.144delC mutation of the Aurora Kinase C gene. Consanguinity at the level of these subjects’ parents appears to be the main risk factor. This situation constitutes a factor of failure of the IVF and leads to direct the couple towards the donation of gametes or the adoption as solution to the parental project.